Development of a proposed single-phase series active power filter without external power sources - Torre, Joao L. (2019)
The quality of electric power is receiving more and more attention from part of consumers, Distribution System Operators (DSO), Transmission System Operators (TSO) and other competent entities related to the electrical power system. Once the electrical Power Quality (PQ) problems have direct implications for business productivity, causing high economic losses, it is mandatory to develop solutions that mitigate these problems. Active Power Filters (APFs) are power electronic equipment capable of compensating PQ problems that have the ability to dynamically adjust their modes of operation in response to changes in load or in the power system. Among these solutions, the Series Active Power Filter (SeAPF) is specially conceived to deal with problems related to the power system voltage amplitude and waveform. Despite the ability to compensate voltage sags, voltage swells, voltage harmonics, and voltage imbalances in three-phase systems, the SeAPF has not achieved much success neither has not been widely adopted. The lack of interest in this equipment can be largely justified by its high cost and also because of some limitations presented by the SeAPF conventional topology. In this paper is presented a novel topology, as well as the control algorithms of a single-phase SeAPF that is connected directly to the power grid without the use of coupling transformers and that does not require the use of external power sources. The topology and control algorithms of the SeAPF proposed in this paper were firstly evaluated by means of simulation results obtained with PSIM software and, once validated, a laboratory prototype was developed, being presented experimental results that support the correct operation of the proposed system.